Normalization of Digital Violence: A Critical Approach - Evgeniya M. Nikolaeva, Polina S. Kotliar, (Opción, 2019)
The article discusses the current situation of the aestheticization of violence in the digital space, which has become the natural result of interaction crises between human beings and the new media. The methodological basis of this study consists of modern philosophical concepts of postmodernism and digital society. As a result, the rational-reflexive attitude to the existing state of affairs is clearly giving way to the elemental aesthetic processes in the digital environment that justify violence. In conclusion, users with a certain set of values generate a unique overall content of the network.